MODEL PEMBELAJARAN BERBASIS ICT (INFORMATION AND COMMUNICATION TECHNOLOGY) DENGAN MENGGUNAKAN MEDIA POWTOON PADA MATA PELAJARAN AKIDAH AKHLAK DI MTS AN-NUURU TIRTOYUDO - Mufidatul Khoiriyah; Maskuri Maskuri; Eko Nasrulloh (VICRATINA, 2021)
Increased educational competition causes schools to flock to updating the institutional education system. Technology can be mastered optimally with the need for adequate knowledge to process and utilize it. Currently, the rapid development of technology gave rise to ICT (Information and Communication Technology). In its development, schools need creative learning models, to be able to complete competitively with other schools. By utilizing facilities and infrastructure and adding them according to the capacity that is a supporting factor for school progress efforts. In its use, ICT has been applied at various levels, ranging from elementary schools, junior high schools, high schools, to universities. There are also quite a lot of learning media, one of the media used is powtoon media which is an application on the website that is useful for making learning videos with interesting animations according to the creativity of each person.